Considerations on the Current Harmonics of Plate-Type Electrostatic Precipitators Power Supplies - Popa, G. N.; Dinis, C. M.; Deaconu, S. I. (Elektronika ir Elektrotechnika, 2013)
Plate-type electrostatic precipitators are the main installations of separating particles from industries (especially for large gas flow) and must operate in its electromagnetic environment without interfering with the operation of other equipments. The power supplies have non-linear elements that cause distortions of the sources currents. The main objective of this work is to analyze measure and simulate currents, voltages and powers from the sources that are used (thyristor-controlled reactor type) taking into account a new electric model, more close to reality, of the ESP sections. It’s analyzed the modification of the current waves shape and THD in case of using passive filters. DOI: http://dx.doi.org/10.5755/j01.eee.19.5.2344